Application research on service innovation and entrepreneurship education in university libraries and archives. (4th May 2020) - Qian, Xiufang; Shi, Huamei; Ge, Chunpeng; Fan, Honghui; Zhao, Xiaorong; Liu, Yijun
College students' innovation and entrepreneurship education is an education to cultivate college students' innovative spirit, entrepreneurial awareness and ability to improve innovation and entrepreneurship. At present, the actual development effect of innovation and entrepreneurship education in China is not obvious. The innovation ability of college students needs to be improved, the proportion of innovation and entrepreneurship is still relatively low, and the success rate of entrepreneurship is not high. Therefore, we suggest that university libraries need to make full use of big data technology to better serve innovation and entrepreneurship education, thus effectively improving the effectiveness of innovation and entrepreneurship education, and facilitating the development of more innovative and entrepreneurial talents. Firstly, it expounds the connotation of innovation and entrepreneurship education, analyses the application of big data in university libraries, and secondly proposes the mechanism of cross-functional collaboration. Then, by integrating the independent data resources of university functional departments, the mechanism overcomes the problem of 'fragmentation'; finally, and innovatively proposed the establishment of new archives, and then through the means of big data for innovation and entrepreneurship education, and ultimately improve the quality of innovation and entrepreneurship education.